Pengembangan Kurikulum Ma’hadi dalam Meningkatkan Kompetensi Mahasiswa - Tsalits, Liqo’ Sa’idatuts; Athiyyaturrahmah, Athiyyaturrahmah; Aisyah, Siti (Asatiza: Jurnal Pendidikan, 2024)
Student Islamic boarding schools are unique and distinctive educational institutions, both in terms of subject (mahasantri) and objects (curriculum and activities). With modernization, the IDIA Prenduan ma'hadi Islamic boarding school provides an adaptive response to adopting a modern education system. This is done by trying to maximize management and curriculum management to produce students who not only have academic knowledge but also instill character values. This research aims to examine the characteristics of the Ma'hadi curriculum and its implications for student character formation. This type of research, field research, in principle relies more on descriptive aspects of data obtained from the field. The results of this research show that the Ma'hadi Islamic boarding school has an educational program that is prepared by itself, where this program contains an educational process that lasts throughout the day in one condition in the dormitory. While IDIA Prenduan uses modern learning methods (tajdid), Ma'hadi Islamic Boarding School has updated its education system with a modern education model where the entire education system starting from teaching techniques, lesson materials, facilities and infrastructure are designed based on the modern education system.